(untitled) - Gillespie, James R. (Australia, 2004)
Modern Livestock and Poultry Production, 8th Edition, entices and engages readers with new, full-color photographs and illustrations, and up-to-date comprehensive information covering agriscience and production information for major and minor livestock and poultry animals. Having undergone extensive updates, the text now includes materials on biosecurity, animal ID, and vertical integration, while still incorporating vital agriscience and production information, including real-life applications, required for high school students’ success in the field. Educators are provided tools like the Instructor’s Guide and the Classmaster CD-ROM, which features a customizable testbank and PowerPoint slides based on the content and organization of the text, to make teaching the subject easier, more interesting and effective. Modern Livestock and Poultry Production, 8th Edition continues to be a widely recommended text by local chapters and the national association of the FFA, which sponsors popular competitions and Career Development Events (CDEs) in livestock and poultry.
Keywords: Livestock,Poultry